2016
DOI: 10.1038/srep26841
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy Study of Intraoperative and Perioperative Serum Intact PTH Level for Successful Parathyroidectomy in 501 Secondary Hyperparathyroidism Patients

Abstract: Parathyroidectomy (PTX) is an effective treatment for severe secondary hyperparathyroidism (SHPT); however, persistent SHPT may occur because of supernumerary and ectopic parathyroids. Here a diagnostic accuracy study of intraoperative and perioperative serum intact parathyroid hormone (iPTH) was performed to predict successful surgery in 501 patients, who received total PTX + autotransplantation without thymectomy. Serum iPTH values before incision (io-iPTH0), 10 and 20 min after removing the last parathyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 22 publications
(29 reference statements)
2
59
0
Order By: Relevance
“…The current patient's iPTH levels were measured at 10 and 20 min after surgical excision of his hyperparathyroid glands and again on the first and fourth days postoperatively. We proved that for TPTX to be successful, there should be a 82.9% decline in serum iPTH levels after 10 min (sensitivity 85.5% and specificity 73.1%) and 88.9% at 20 min (sensitivity 78.6% and specificity 88.5%) . Blood iPTH >100.5 pg/mL on day 1 (sensitivity 100% and specificity 98.6%) and iPTH >147.4 pg/mL on day 4 (sensitivity 100% and specificity 99.5%) after the operation are considered indicative of persistent SHPT .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The current patient's iPTH levels were measured at 10 and 20 min after surgical excision of his hyperparathyroid glands and again on the first and fourth days postoperatively. We proved that for TPTX to be successful, there should be a 82.9% decline in serum iPTH levels after 10 min (sensitivity 85.5% and specificity 73.1%) and 88.9% at 20 min (sensitivity 78.6% and specificity 88.5%) . Blood iPTH >100.5 pg/mL on day 1 (sensitivity 100% and specificity 98.6%) and iPTH >147.4 pg/mL on day 4 (sensitivity 100% and specificity 99.5%) after the operation are considered indicative of persistent SHPT .…”
Section: Discussionmentioning
confidence: 81%
“…. Serum iPTH levels were measured using a UniCel DxI800 Access Immunoassy System (Beckman Coulter, Inc., Fullerton, CA, USA) . Vitamin D and calcium (Ca) supplements were prescribed.…”
Section: Casementioning
confidence: 99%
“…They found excellent correlation between both assays and because of its accuracy it permits a reduction of operating time [11]. In a short-term study, Zhang et al [4] evaluated the diagnostic accuracy of ioPTH in predicting successful PTX in 501 secondary HPT patients. In 89% or more of cases, ioPTH could predict successful PTX with a sensitivity rate of 78.6% and specificity rate of 88.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Moor et al[15] showed that after PTX, patients are required to have long-term calcium and PTH assay follow-up because of tenacious hypoparathyroidism, as normoparathyroidism cannot be achieved. Zhang et al[4] defined successful PTX as iPTH <300 pg/mL after PTX. Overall, the mean percentage reduction of serum iPTH at 10 and 20 min after PTX in the successful PTX group were 86.8 and 90.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation